2008
DOI: 10.1002/ijc.23821
|View full text |Cite
|
Sign up to set email alerts
|

Leptin promotes motility and invasiveness in human colon cancer cells by activating multiple signal‐transduction pathways

Abstract: Leptin serum levels are about 5 times higher in obese people than in normal individuals. We aimed at investigating the signaling pathways induced by leptin in the human colonic cell lines LS174T and HM7. Both cells expressed the leptin transmembrane Ob-receptor. Leptin activated the mitogen-activated protein kinase pathway, induced invasion of colonic cells and concomitantly increased the formation of lamellipodial structures. A direct and novel dose-and time-dependent activation of RhoA, Cdc42 and Rac1 by lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
103
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 70 publications
7
103
1
1
Order By: Relevance
“…47,49,50 Experimental studies have also shown that leptin, related to the amount of adipose tissue, is increased by excessive energy intake 51 and promotes human colonic cell proliferation and invasiveness in colon cancer. 52,53 In our study, significantly increased CRC risk with obesityrelated anthropometric variables was confined to women. This finding is in contrast with the results from previous studies including several meta-analyses that have shown that obese men, estimated by BMI, are more likely to develop CRC than obese women.…”
Section: Discussionmentioning
confidence: 45%
“…47,49,50 Experimental studies have also shown that leptin, related to the amount of adipose tissue, is increased by excessive energy intake 51 and promotes human colonic cell proliferation and invasiveness in colon cancer. 52,53 In our study, significantly increased CRC risk with obesityrelated anthropometric variables was confined to women. This finding is in contrast with the results from previous studies including several meta-analyses that have shown that obese men, estimated by BMI, are more likely to develop CRC than obese women.…”
Section: Discussionmentioning
confidence: 45%
“…40 Leptin also modulates the proliferation of colon adenocarcinoma cancer cells LS174T and HM7; this process possibly takes place through Src and PI3K signaling, which is known to promote colon carcinogenesis and metastasis. 41 Other in vitro studies have suggested that these hormones stimulate the PI3K/Akt pathway and induce the phosphorylation of ERK pathways, thus activating these signaltransduction pathways associated with cell growth. 42,43 The compensatory hyperinsulinemia in obesity also leads to the release of intracellular mediators involved in growth factor signaling, which activate proto-oncogene p21Ras.…”
Section: Discussionmentioning
confidence: 99%
“…The Src/PI3K/Akt pathway is highly activated by multiple cancer risk factors which are elevated in obesity [Jaffe and Schwartz, 2008;Huang and Chen, 2009b]. These factors include increased blood levels of insulin, IGF-1, leptin, TNF-alpha, and IL-6.…”
Section: Activation Of the Src/pi3k/akt Signal Pathway In Obesitymentioning
confidence: 99%
“…These factors include increased blood levels of insulin, IGF-1, leptin, TNF-alpha, and IL-6. These factors have been demonstrated to activate Src/PI3K/Akt to promote carcinogenesis [Jaffe and Schwartz, 2008;Roberts et al, 2009;Huang and Chen, 2009b]. In addition, decreased blood level of adiponectin in obesity also contributes to the action of the pathway as adiponectin can block insulin and leptin [Fujisawa et al, 2008;Huang and Chen, 2009a].…”
Section: Activation Of the Src/pi3k/akt Signal Pathway In Obesitymentioning
confidence: 99%